2019
DOI: 10.1186/s40854-019-0123-7
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and FDI: evidence from developed and developing countries

Abstract: This study investigates the impact of institutional quality on Foreign Direct Investment (FDI) inflows using panel data for low, lower-middle, upper-middle and high-income countries for the sample period of 1996-2016 using the system Generalized Method of Moments (GMM). The empirical results confirm that institutional quality has a positive impact on FDI in all group of countries. The magnitude of the coefficients of control of corruption, government effectiveness, political stability, regulatory quality, rule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
137
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(198 citation statements)
references
References 48 publications
17
137
0
10
Order By: Relevance
“…With appropriate Chinese investor decisions and a favorable business environment in the host countries, the efficiency of Chinese OFDI could be significantly improved [2]. However, as most existing studies have analyzed Chinese OFDI location choice determinants based on aggregate OFDI data [3][4][5][6][7][8][9], the specific determinants in each industry have not been distinguished. Further, because of potential extreme values, aggregate OFDI data can suffer from skewed data structures, which may adversely affect model fit and estimations [10].…”
Section: Introductionmentioning
confidence: 99%
“…With appropriate Chinese investor decisions and a favorable business environment in the host countries, the efficiency of Chinese OFDI could be significantly improved [2]. However, as most existing studies have analyzed Chinese OFDI location choice determinants based on aggregate OFDI data [3][4][5][6][7][8][9], the specific determinants in each industry have not been distinguished. Further, because of potential extreme values, aggregate OFDI data can suffer from skewed data structures, which may adversely affect model fit and estimations [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the developing countries, the institutional quality effect was insignificant because of the weak structure of institutions. However, in the most recent study of Sabir et al (2019) the positive relationship between institutional quality and FDI was reported for all groups of countries from low, lower-middle, upper-middle to high-income ones.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Results reveal that the improvement of the institutional framework should precede foreign direct investment attraction policies in order to benefit FDI-led growth. Sabir (2019) this paper examines the impact of institutional quality on foreign direct investment inflows using panel data for income countries (low, lower-middle, upper-middle, high). Using a sample period from 1996-2016.…”
Section: Business and Economic Researchmentioning
confidence: 99%